Effects of Neurotrophin-3 Plasmids on Myocyte Apoptosis and Ca²⁺-ATPase Content in the Muscle After Nerve Injury in Rats - Dong, Yu.; Zhao, H.; Yang, L.; Zhao, Yi.; Ma, Ch.; Zhang, Ch. (Нейрофизиология, 2015)
We estimated the influence of plasmids with DNA carrying the neurotrophin-3 (NT-3) gene on apoptosis in the gastrocnemius muscle and content of Ca²⁺-ATPase in the latter after sciatic nerve injury. Sixty adult Wistar rats were randomly divided into the saline (control) and NT-3 groups. The related indices, such as expression of caspase-3 protein, the rate of apoptosis in the muscle evaluated using a TUNEL technique, and the level of Ca²⁺-ATPase estimated using Western blot, were observed. Expression of caspase-3 protein was elevated at different post-operative times after peripheral nerve injury; NT-3 expression and the rate of muscle cell apoptosis decreased, whereas the level of Ca²⁺-ATPase in the sarcoplasmic reticulum increased; significant differences were observed compared with the saline group (P < 0.05). The mitigation mechanism of NT-3 on muscle atrophy after peripheral nerve injury is expressed as inhibition of caspase-3 gene expression, increase in the Ca²⁺-ATPase level, and reduction in the rate of muscle apoptosis.